The Word That Did (Not) Escape – ovde [here] and tamo [there] - Miloradović, Sofija R. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This contribution first establishes a link between Paraćinsko Pomoravlje and Kosovo and Metohija through the poetics of five dialect texts. Then, via the antonymically positioned adverbial pair ovde and tamo, it draws attention to the contrast between the present place of residence and the past homeland, between the homeland and the foreign land, this world and the otherworld. The concerned two words are key words of sorts, describing the life of individuals and families – not merely in space but in time as well, and including their way of life. The basic lexicographic definition of the adverb ovde is “here, in this place”, and of the adverb tamo “there, in that place”, but in the story of our sufferers, tamo denotes the homeland, the place they were exiled from, and therefore – something familiar and close, while in two other cases the word tamo symbolizes something distant, unknown and frightening – foreign lands and death. Additionally, however, the secondary dictionary meaning of the adverb ovde – “here, towards this place”, linked to verbs of motion, reflects the speakers’ migrations to some future places of residence.
Keywords: adverbial pair ovde and tamo; Kosovo and Metohija; Paraćinsko Pomoravlje